Globalisation and Resistance: Law Reform in Asia Since the Crisis - Feerst, Alex (Columbia Journal of Asian Law, 2007)
Globalization, a survey of recent titles reveals, has its enemies, defenders, cultures, servants, and discontents. This book focuses on some of its resisters. At the center of this collection is the legalization process by which Asian nations have moved in recent years toward more formalized, less autonomous, legal structures. Derived from a 2003 workshop at the International Institute for the Sociology of Law in Ofiati, Spain, the ten essays in Globalisation and Resistance: Law Reform in Asia Since the Crisis employ perspectives including modernization theory, institutional economics, and Weberian rationalization theory, to explore how globalization has played out in nations such as India, Indonesia, Malaysia, South Korea, Thailand, and China. Editors Christoph Antons and Volkmar Gessner locate this collection at the intersection of empirical methodology and Asian geography, where a relative gap exists in law and development literature. In the theory-oriented field of globalization studies, they argue, it is through empiricism that one avoids formalist “rule of law optimism” and the attendant problems of implementation blindness and cultural tone- deafness. Case studies and institutional analysis are presented as ways to acquire indispensable local knowledge. Thematically, the varied chapters are organized around the tension between forces of globalization and oppositional local practices in the wake of two major events – the Asian Financial Crisis of 1997 and the 9/11 terrorist attacks. Serially, they attest to the multiplicity of relations among national, transnational, global, and local forces in legal reform.